Menyelami Aspek Kejurnalistikan dalam Ekspresi Ayat-ayat Al-Qur’an - Fahrurrozi Fahrurrozi (Universitas Islam Negeri Mataram, 2011)
The cohesion between al-Qur’an and journalism bringing along deep and wide influences. Al-Qur’an is “God’s words” whilst journalism is “Man’s writing”; al-Qur’an derives from God The Creator, whilst man’s writing functions as tool to express everything, God’s creations. The qalam, writings, basically functions as medium to deliver knowledge that can not be well revealed without process of human reading and interpretation. Qalam, textuality, is considered more solid than kalâm, orality. The former which has no intonation can produce crativity when man read it and lead to new culture; whilst the latter which has pressure and accentuation tends only to preserve the existing culture, leaving no space for creativity. That is why text reflection is considered more reliable than oral references.